BURONG TILAPIA: FACTORS ON THE FERMENTATION PROCESS AND ITS MICROBIOTA (Samota Journal of Biological Sciences, 2024)
Fermented fish products hold significant prominence in the Philippines. However, its potential risks for human consumption are faced as a result of inadequate awareness of microbiological standards in its preparation. This study investigated the microbiota and fermentation process of burong tilapia, how this is influenced by fermentation factors such as salt content, temperature, and proper sanitation, and how it can impact food safety for human consumption. This study revealed that the population of aerobic microorganisms in burong tilapia was relatively high with the Aerobic Plate Count result of 2.1 x 107 CFU/g, indicating significant bacterial presence. On the other hand, a relatively low level of E. coli and Yeast and Molds count was detected having
Keywords: Fermentation of fish; Aerobic plate count; Food quality and safety